Staphylococcus aureus persistence in the lung is necessary to elicit systemic protective immunity - Chidella, Usha Vyshnavi; Li, Zhaotao; Kleinhenz, Maureen; Montgomery, Christopher P. (Frontiers in Immunology, 2025)
Staphylococcus aureus is a leading cause of skin and soft tissue infections (SSTI) and pneumonia. Recurrence is common and treatment is complicated by antimicrobial resistance; therefore, it is necessary to understand the mechanisms by which the host develops protective immunity against S. aureus. We previously reported that SSTI, but not pneumonia, elicits strong S. aureus-specific antibody and T cell responses and protection against recurrent infection; these findings suggested that site-specific elicited immune responses drive protective immunity. Because S. aureus is rapidly cleared from the lung but persists in the skin, we hypothesized that bacterial persistence in the lung is necessary to elicit protective antibody and T cell responses. In this study, we tested this hypothesis using a newly described mouse model of persistent pneumonia. Indeed, persistent pneumonia and SSTI elicited strong toxin-specific antibody and CD4+ IL-17+ and IFNγ+ T cell responses, whereas transient pneumonia did not. Persistence of S. aureus in the lung was accompanied by durable systemic T and B cell expansion observed as early as 9 days after infection. Consistent with important roles for antibodies and T cells in protective immunity, SSTI and persistent pneumonia, but not transient pneumonia, elicited protection against secondary SSTI and pneumonia. Taken together, these results demonstrate that bacterial persistence in infected tissues is necessary to elicit protective immunity against recurrent infections. These findings have important implications in better understanding the mechanisms of natural immunity against S. aureus.